Sistem Pembelian Bahan Material Produksi Divisi Purchasing Pada PT Grand Twinss Engineering - Safitri, Gita; Kamila, Nurul (JURNAL MAHASISWA BINA INSANI, 2023)
This research has a background so that companies can carry out the process of purchasing production materials. This research aims to find out how the purchasing process is the effort made to buy goods that are needed for the company. Raw material inventory is an important factor in a company to support the smooth production process. The method used in this research is observation, namely direct observation of the purchasing process in the purchasing division at PT Grand Twinss Engineering, then the interview consists of asking several questions to the purchasing division at PT Grand Twinss Engineering with questions related to the material being discussed. is in this journal. The results of this research are that the purchasing process at PT Grand Twinss Engineering has gone well, but there are obstacles found, namely when handing over complete documents, they still use a handwritten manual system, but these problems will be overcome by having Created Outstanding Purchasing to make it easier for the purchasing division to submit documents to the accounting division